EFFORTS TO FOSTER AND COUNSELING BHABINKAMTIBMAS IN THE PREVENTION OF MOTOR VEHICLE THEFT IN THE WONOSOBO POLICE JURISDICTION - PALTI MADELINO (Indonesian Journal of Police Studies, 2022)
This research was motivated by the phenomenon of motor vehicle theft which increased the Wonosobo Police In 2019 to 2021. This is one of the ineffectiveness of Bhabinkamtibmas function in carrying out coaching and counseling activities as a preventive effort from the police. Analyzed using management theory and communication theory. The goal is to prevent the criminal act of theft of motor vehicles and factors that affect its implementation. This research uses a qualitative research approach that demands the knowledge of researchers in understanding the object of research aimed at describing the implementation of coaching and counseling activities, and informing the efforts made by Bhabinkamtibmas in preventing curanmor crimes and what factors affect Bhabinkamtibmas kineja in carrying out coaching and counseling to prevent curanmor crimes. Data collection techniques performed in this writing are by interviewing, observation or observation, and document studies. The results of the research showed that the implementation of coaching and counseling has been carried out but has not been maximized so that there are still many motor vehicle theft crimes. Factors that affect Bhabinkamtibmas efforts are Bhabinkamtibmas personnel who are still lacking and not yet in accordance with Perkap no.7 of 2021, inadequate facilities and infrastructure, Bhabinkamtibmas personnel who have not attended vocational education, Bhabinkamtibmas inventarsis goods that have begun to be damaged. Based on the results of the study, recommend conclusions and suggestions that, increase the number of personnel, provide vocational education to Bhabinkamtibmas personnel, and add infrastructure to support Bhabinkamtibmas activities